Siriraj I Gγ(aγδβ)-thalassaemia Causing Severe Thalassaemia Intermedia In Compound Heterozygous State With IVS1-1(G→T) Mutation - Ying Ying Wong; Hafiza Alauddin; Raja Zahratul Azma Raja Sabudin; Azlin Ithnin; Norunaluwar Jalil; Zarina Abdul Latiff; C-Khai Loh; Hamidah Alias; Ainoon Othman (College of Pathologists, Academy of Medicine Malaysia, 2024)
Indexed by WOS/ Scopus/ MyCite